Educational leadership in Portugal:navigating ethics, morality, and future trends - Neves, Maria de Lurdes (Frontiers in Education, 2025)
The school, as the basic unit and a space for the achievement of objectives and goals of the education system, is constantly being renovated, becoming a major challenge for the directors, because it requires of them new skills, knowledge, abilities and attitudes that converge in the need of development of skills for making the decisions more participatory and fair. This study goal is to identify in 30 educational directors of school groups, their leadership perceptions and practices. As a method to achieve this goal, a mix study has been carried out using semi-structured interviews and three leadership scales (ethical, moral and transformational). As results it was found that the leadership perceptions vary between transactional and transformational and that some leadership skills are predictors of the type of leadership exercised. Future studies are needed about leadership, different styles and cultural organizational context variables.